2018
DOI: 10.1007/s00264-018-3998-4
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late treatment of paediatric femoral neck fractures: a systematic review and meta-analysis

Abstract: II/III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Risk factors for the development of AVN are diverse. Studies have suggested patient’s age, gender, type of fracture, capsular decompression, time to surgery, and method of fixation as independent risk factors for the same [ 6 , 12 - 13 , 18 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for the development of AVN are diverse. Studies have suggested patient’s age, gender, type of fracture, capsular decompression, time to surgery, and method of fixation as independent risk factors for the same [ 6 , 12 - 13 , 18 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] They are frequently associated with high-energy trauma such as falling from a significant height, as in the case of this patient, or from high-speed motor vehicle accidents. [1][2][3][4] Since the femoral head is exclusively supplied by the lateral epiphyseal artery with no anastomosis between the epiphysis and femoral neck, injury to this area can lead to complications such as avascular necrosis (AVN), bone non-union, coxa vara, chondrolysis, premature physeal closure, and infection. 2 AVN is the most common and serious complication, and the rate of AVN varies significantly between 0% -92% among different reports.…”
Section: Discussionmentioning
confidence: 95%
“…2 AVN is the most common and serious complication, and the rate of AVN varies significantly between 0% -92% among different reports. 1 Surgical reduction of femoral neck fracture with either closed or open internal fixation realign the bone to preserve vascular supplies and prevent the progression of AVN and nonunion. 3 Study shows that patients with delayed surgical intervention of >24 hours were 4.5 times more likely to develop AVN compared to early intervention of < 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations